Dr. Tang Ho — Deep Plane Facelift — Houston - Ho, Tang (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Tang Ho, practicing in Houston, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003024; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; houston